Die PKW-Maut: Ein Appell an die ökonomische Vernunft. - Schröder, Michael (Deutscher Verkehrs-Verlag, 2005)
Die verursachergerechte Bepreisung des motorisierten Individualverkehrs scheitert seit Jahrzehnten an mangelnder gesellschaftlicher Akzeptanz. Vor dem Hintergrund zunehmender Stauungen auf der Straße, verbunden mit neuen verfügbaren Informations- und Kommunikationstechnologien, müssen Argumente für die Einführung eines den Verkehr entzerrenden Preismechanismus verständlich, aber heute massiv in die Öffentlichkeit getragen werden. difu

According to transportation science-related findings, road congestion plus wear and tear, especially in the case of Germany's federal motorways, cannot be blamed only on heavy goods vehicles. Since competition nowadays is increasingly dominated by issues of time and geography-related factors tend to give way time-related ones, traffic congestion caused by infrastructure problems is seen more than in the past as a negative element directly linked to a given location. In the case of motorized personal travel, the introduction of a general user charge linked to the actual cause and level of congestion would have a favourable effect on traffic from the aspects of time and space. For the indiviudals involved, any costs associated with road user charges would be balanced out by other advantages. The current traffic-related tax, which does not have any influence on the traffic as such, is to be replaced by a multi-level set of charges related directly to causes of congestion. This makes economic sense, is technically feasible and could be introduced right now. difu
Keywords: Individualverkehr; Personenkraftwagenverkehr; Straßenverkehr; Gebühr; Autobahn; Verkehrsweg; Kosten; Verkehrsinfrastruktur; Maut; Autobahngebühr; Straßenbenutzungsgebühr